MEKANISME VERIFIKASI SUARA PENDUKUNG CALON KEPALA DAERAH PERSEORANGAN DALAM UNDANG-UNDANG NOMOR 10 TAHUN 2016 TENTANG PEMILIHAN KEPALA DAERAH - M. Saada Hilman; Dessy Artina; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Indonesia is a constitutional state as stated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. The concept of a rule of law cannot be separated from the concept called democracy. One of the parameters for the development of democracy and people's sovereignty in Indonesia is reflected in the General Election. It is stated in Article 28D paragraph (3) of the 1945 Constitution which states that,